POLA KOMUNIKASI JURNALISTIK DALAM PERSPEKTIF ISLAM - Susanto, Agus (Jurnal Ilmiah Al-Hadi, 2018)
The development of information technology today has experienced very rapid progress. Various communication media compete in providing information without limits. The world is now and is changing, rolling in the process of information and communication revolution that gave birth to a new civilization, making it easier for humans to interact and increase social mobility. Inevitably, today's society has turned into a society that is very dependent on information technology today, both for the sake of knowledge, academics, entertainment, commerce and the spread of certain religions and so on. The development of information technology does not always have a positive impact on human life, even some academics and experts actually worry about the negative impacts brought by the flow of information technology advancements at this time. On the other hand, this can be an effective medium for human improvement or improvement in a better and advanced direction. Including being an effective medium in the development of religion (Islam) or specifically for the benefit and development of future da'wah. One of the da'wah media used is the da'wah bil qolam or da'wah with a pen which is currently synonymous with the world of journalism that is very attached to the utilization of the development of information technology. Therefore journalism as an instrument of da'wah communication must really be utilized to the maximum extent possible for the development and effectiveness of Da'wah itself. Therefore, the fundamental principles and ethics in journalistic communication according to the Islamic view by utilizing the information technology must be a moral foundation held firmly by journalists/actors so as to bring the benefit of the people and theattainment of the objectives of Islamic da'wah effectively and comprehensively.